The Octagon in the Houses of Orson Fowler - Eliseu Gonçalves (2011)
Orson Squire Fowler (1809-1887) was an American author who wrote a fantastic book about octagonal houses in the mid-nineteenth century. This present essay focuses on how radial geometry can be used as a tool placed for designing comfortable, affordable housing. Octagonal geometry can be used as a tool for controlling nature, or as a system for controlling construction. This duality is synthesized in Fowler's use of the octagon. The analysis is extended to two other buildings with octagonal plans, one ancient, the Hellenic "Tower of the Winds," the other contemporary, Alvaro Siza's "Mickey Mouse House.".